The importance of ketamine for cerebral protection in pediatric cardiac surgery - A. A. Ivkin; E. V. Grigoriev (Вестник анестезиологии и реаниматологии)
The problem of cerebral protection in cardiac surgery is relevant, despite all the techniques used. Due to its properties, ketamine can occupy its niche in solving this problem. The article analyzes current literature sources and describes the use of ketamine for analgesia, sedation and cerebral protection, and analyzes its properties for reducing the systemic inflammatory response. The mechanisms of its action and recommended doses are given, and schemes for its use both during anesthesia and the postoperative period are presented.